2005
DOI: 10.1007/s00213-005-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between nicotine and nonpharmacological stimuli reveal multiple roles for nicotine in reinforcement

Abstract: Although considerable progress has been made we do not yet fully understand the behavioral and neurobiological bases of nicotine reinforcement, and without this knowledge treatment strategies aimed at reducing smoking remain deficient. This dissertation provides an original perspective on nicotine reinforcement, which arises from substantial evidence of complex interactions between nicotine and nonpharmacological stimuli. The present experiments tested the hypothesis that nicotine reinforcement derives from at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
217
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(235 citation statements)
references
References 170 publications
(331 reference statements)
14
217
3
1
Order By: Relevance
“…First, nicotine directly strengthens operant responding (primary reinforcing effect, see Chaudhri et al, 2006). Second, nicotine enhances the incentive value of reinforcing nonpharmacological stimuli Donny et al, 2003;Palmatier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…First, nicotine directly strengthens operant responding (primary reinforcing effect, see Chaudhri et al, 2006). Second, nicotine enhances the incentive value of reinforcing nonpharmacological stimuli Donny et al, 2003;Palmatier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Elovainio et al (2005) demonstrated that the effect of dopamine D4 receptor genotype on smoking behavior was mediated by NS. Third, systems involved in processing and responding to appetitive, aversive, and novel stimuli that are related to TCI temperament dimensions may also underlie smoking behavior (Chaudhri et al, 2006). Specifically, responding to aversive stimuli, such as the physical sensations of nicotine withdrawal, may be exaggerated in individuals with particular TCI profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent use and dependence on tobacco is mediated primarily, but not exclusively, by nicotine (Chaudhri et al, 2005b;Wonnacott et al, 2005). Sex is an important factor that mediates the neurobiological response to nicotine, and ultimately the course of dependence behavior in humans that abuse cigarettes.…”
Section: Introductionmentioning
confidence: 99%